UNVEILING THE DIGITAL BOUTIQUE EXPERIENCE: AN EXPLORATORY FACTOR ANALYSIS IN THE FASHION INDUSTRY - Rohman, Fatchur; Firdausiah, RR Ayu; Parwati, Kardina Yudha (Veredas do Direito, 2025)
The development of digital technology has changed consumption behavior in the fashion industry. Internet access and the availability of e-commerce allow customers to shop anywhere and anytime without visiting a boutique. These changes in consumer behavior make creating shopping experiences on digital media important to pay attention to. This study aims to validate the measurement of digital boutique experience as a major factor influencing customer behavior in digital boutiques. This research uses a quantitative method with a purposive sampling technique. Data were collected through an online survey using a questionnaire filled out by 204 digital boutique customers. The questionnaire consists of 24 statement items designed to identify the dimensions of the digital boutique experience. Exploratory Factor Analysis (EFA) was used to refine the measurement instrument and confirm the factor structure underlying the digital boutique experience. The results show that the digital boutique experience in the fashion industry is influenced by four main dimensions: seamless experience, Trustworthiness, customer support, and digital content-driven. The findings make a theoretical contribution to understanding the key factors that shape customer experience in digital boutiques and provide practical implications for digital boutique managers in designing more effective strategies to increase customer engagement and loyalty.